2010
DOI: 10.1111/j.1462-2920.2010.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of virus–host systems in hypersaline Lake Retba, Senegal

Abstract: Remarkable morphological diversity of virus-like particles was observed by transmission electron microscopy in a hypersaline water sample from Lake Retba, Senegal. The majority of particles morphologically resembled hyperthermophilic archaeal DNA viruses isolated from extreme geothermal environments. Some hypersaline viral morphotypes have not been previously observed in nature, and less than 1% of observed particles had a head-and-tail morphology, which is typical for bacterial DNA viruses. Culture-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 70 publications
3
112
0
Order By: Relevance
“…Surprising was the observation of spindle-shaped (tailed or tailless) (Figures 3a-e) or rod-shaped (Figures 3f and g) particles that was similar to VLPs previously reported from geothermal and hypersaline environments (Bath et al, 2006;Prangishvili, 2006;Sime-Ngando et al, 2011). Four types of complex viral forms (Figures 3h-n) were also never reported from freshwater systems.…”
Section: Phenotypic Diversity Of Virusesmentioning
confidence: 78%
See 1 more Smart Citation
“…Surprising was the observation of spindle-shaped (tailed or tailless) (Figures 3a-e) or rod-shaped (Figures 3f and g) particles that was similar to VLPs previously reported from geothermal and hypersaline environments (Bath et al, 2006;Prangishvili, 2006;Sime-Ngando et al, 2011). Four types of complex viral forms (Figures 3h-n) were also never reported from freshwater systems.…”
Section: Phenotypic Diversity Of Virusesmentioning
confidence: 78%
“…The observed spindle-shaped tailless particles (Figures 3a and b) resembled virions of members of the family Fuselloviridae and the unassigned genus Salterprovirus, whereas tailed spindle-shaped VLPs (Figures 3c-e) resembled members of the family Bicaudaviridae Pina et al, 2011). Such particles are abundant in extreme geothermal and hypersaline environments (Prangishvili, 2006;Sime-Ngando et al, 2011) but, to our knowledge, were never observed in habitats at moderate temperature and salinity. Moreover, none of these virion morphotypes is known to be associated with bacteria or eukaryotes.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, all currently isolated viruses of euryarchaea fall into three morphological groups: (i) head and tail (resembling bacterial viruses of the order Caudovirales), (ii) tailless icosahedral, and (iii) spindle shaped/ pleomorphic (212,236). However, a recent sampling of the viral diversity in saltern ponds, a beloved habitat of halophilic archaea, unveiled that our current knowledge of the diversity of euryarchaeal viruses is far from complete; viral morphotypes previously thought to be specific to crenarchaeal viruses are also present in hypersaline environments (252).…”
Section: Euryarchaeal Virusesmentioning
confidence: 99%
“…Nevertheless, it has already allowed the identification of several thousands of viruses having different morphologies and characteristics, and also of new virus families (see review in Le Romancer et al, 2007). Viruses have been identified in all known extreme environments: hypersaline (Oren et al, 1997;Dyall-Smith et al, 2003;Pagaling et al, 2007;Sime-Ngando et al, 2010), alkaline lakes (Jiang et al, 2004), deserts (Prigent et al, 2005), polar regions (Maranger et al, 1994;Kepner et al, 1998;Borriss et al, 2003;Gowing, 2003), acid mine drainages (Kyle et al, 2008a), deep subsurface rocks (Bird et al, 2001;Kyle et al, 2008b), and in hydrothermal environments. The search for new viruses in the latter environment has been especially fruitful, following the pioneering work of Wolfram Zillig on the viruses of hyperthermophilic Archaea (Martin et al, 1984;Rice et al, 2001;Rachel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%